U ŹRÓDEŁ ZASADY ‘AUDIATUR ET ALTERA PARS’ - Zabłocka, Maria (Zeszyty Prawnicze, 2017)
At the Root of the Principle of ‘audiatur et altera pars’ Summary The aim of the article is to show that the prototype of what later became the principle of audiatur et altera pars is a provision from Law 1,7 of the Twelve Tables, cum perorando ambo praesentes (let them speak when both are present). At the start of proceedings both parties were to put their case to the praetor; in other words both parties presented their evidence in the presence of the opposite party. This concise provision encapsulates the fundamental principles judges in modern civil proceedings are expected to observe: audi alteram partem (“hear the other side”), equal treatment of both parties, and direct examination of the evidence. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />